Nursing Home Care in Families with Problems Hypertension Health - A. Syamsinar Asmi; Hermin Husaeni (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Increasing awareness, willingness and ability to live a healthy life for everyone so that an optimal degree of public health can be achieved through the creation of the nation's people and the Indonesian state, the population lives in a healthy environment and behavior and has a fair and equitable quality of health. The purpose of the study was to obtain a real picture of the implementation of home care case studies in families with hypertension health problems. The research method that will be used is a case study using a systematic approach to family nursing to obtain complete data with the method; interview, observation. The results showed that in the preparation of a family nursing care plan, the writer gained real experience about applying care directly to the target family. Conclusions on family care should use a systematic approach to identifying health problems appropriately and increasing information provided by health workers to improve family and community understanding of an illness and health problems related to people's lives, through prevention, and health promotion